PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KOMITMEN ORGANISASI SERTA DAMPAKNYA TERHADAP KINERJA GURU SMK MUHAMMADIYAH SALATIGA - Samtono Samtono (Among Makarti, 2017)
Abstract            The  purpose  of  the  research  is  to examine  and  analyze   the influence  of  the organizational  culture  and  principle’s   leadhership  and  commitment  organizational  and  its affect  on  teacher’s  performance  in  SMK Muhammadiyah  Salatiga. The  research  was conducted  to high  school  teacher  of  SMK  Muhammadiyah  Salatiga  as  many  as  65  respondents.            The  data  obtained  were  processed  using  descriptive  analysis  and  multiple regression  analysis  to  determine  the  affect  of  independent  variables  on  the  dependent variables. The  show  that  ( 1 )  The  organizational  culture  has  positive  affect  to  commitment organizational,      ( 2 ) The  principle’s  leadhership  has  negative  affect   to commitment  organizational, ( 3 )  The  commitment  organizational  has  positive  affect  to  teacher’s   performance, ( 4 ) The  principle’s  leadhership  has  negative  affect  to  teacher’s performance, ( 5 ) The  commitment  organizational  has  positive  affect  to  teacher’s performance, ( 6 ) The influence  of  organizational  culture  to  the  commitment  organizational  positive  affect  to  teacher’s  performance, ( 7 ) The  influence  of  the  principle’s  leadhership to  the  commitment  organizational  positive  affect  the  theachr’s  performance. Keywords :  The Organizational  culture,  Principle’s  Leadhership,  Organizational                     Commitment, Teacher’s Performance.